2015
DOI: 10.1177/1039856215593397
|View full text |Cite
|
Sign up to set email alerts
|

Recovery-based services in a psychiatric intensive care unit – the consumer perspective

Abstract: Recovery principles can be successfully introduced in a psychiatric intensive care unit environment. Introduction of recovery based practice was associated with a reduction in seclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…In total, 35 publications were included in this review 4 6 23-55 which reported on seclusion, 23 56 is reported in figure 1.…”
Section: Included Studiesmentioning
confidence: 99%
“…In total, 35 publications were included in this review 4 6 23-55 which reported on seclusion, 23 56 is reported in figure 1.…”
Section: Included Studiesmentioning
confidence: 99%
“…From the patients’ perspective, recovery‐based and person‐centred care can provide useful theoretical frameworks relevant for sensory rooms on psychiatric wards, including the concept of being a ‘person’, the importance of the care environment, choice and responsibility, risk awareness and management, as well as different forms of knowing (Ash et al . ; Björkdahl et al . ; McCormack & McCance ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the value of engagement in meaningful and enjoyable activities in hyperacute settings has been highlighted by numerous authors (Ash et al ., ; Best, ; Gwinner & Ward, ; Salzmann‐Erikson et al ., ; Sullivan et al ., ), previous studies have not attempted to describe the types of activities that might be most suitable for individuals admitted to these units. As was described in the introduction, ‘typical’ occupational therapy groups and activities used in general acute settings may not be appropriate for individuals experiencing high levels of acute symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Although the practice description provided by Best (1996) is very useful, it is based predominantly on one person's experience and provides only anecdotal information. Other literature also supports the importance of occupational therapy or meaningful activities in the context of PICUs or HDUs (Ash, Suetan, Nair & Halpin, 2015;Gwinner & Ward, 2014;Pereira & Woollaston, 2007;Salzmann-Erikson, L€ utz en, Ivarsson & Eriksson, 2011;Sullivan et al, 2004), but there is very little specific information about the types of activities that are helpful or specific approaches that should be taken by occupational therapists in these settings. This lack of specificity is consistent with findings from Crowhurst and Bowers (2002) who reported that there was a lack of specific intervention guidelines for treatment approaches in PICUs.…”
Section: Evidence For Occupational Therapy In Picus and Hdusmentioning
confidence: 99%
See 1 more Smart Citation